THERMAL PERFORMANCE ANALYSIS OF FUEL GAS PREHEATERS USING CFD TECHNIQUES - Nofrizalidris Darlis; Kamariah Md Isa; Kahar Osman; Thivaakar Rajaratinam; Nur Hazwani Mokhtar; Ab Aziz Mohd Yusof; Aminuddin Saat (Applications of Computational Fluid Dynamics in Mechanical Engineering (Series 4), 2025)
Gas turbines have been a cornerstone of power generation technology since their introduction in 1939, operating through the continuous interaction of air compression, fuel combustion, and turbine expansion. Modern designs employ axial compressors equipped with inlet guide vanes (IGV) and variable guide vanes (VGV) to enhance airflow control and efficiency. This study focuses on the optimisation of fluid velocities within a fuel gas preheater, an essential component in gas turbine systems. Using computational fluid dynamics (CFD) analysis, various flow conditions were evaluated to determine their impact on thermal performance. The results revealed that setting the natural gas velocity at 5 m/s and the water velocity at 1 m/s produced the most favourable outcomes, yielding the highest temperature rise, superior heat transfer rates, and a notable pressure drop on the shell side, indicative of enhanced energy exchange. Among the CFD models tested, the k–? turbulence model coupled with a pressure-based solver demonstrated the most accurate and physically consistent predictions. These findings underscore the importance of optimised flow dynamics in improving heat exchanger efficiency and provide valuable insights for advancing gas turbine performance and energy system design. Keywords: Gas Turbine, Fuel Gas Preheater, Computational Fluid Dynamics (CFD), Heat Transfer